Development of a facial anamnesis form for the pharmaceutical prescription of dermocosmetics - Oliveira , Ariadine Aparecida de; Moraes, Talita Cristina M.; Herrerias, Tatiana (Seven Editora, 2023)
The objective of this study was to develop a facial anamnesis form that can serve as an instrument to guide pharmacists in the prescription of dermocosmetics, a special-ized category of skin care products, which differ from traditional cosmetics by provid-ing support in the control of various situations and even pathologies. The anamnesis form was prepared based on the scientific literature of the Scientific Electronic Li-brary Online (Scielo), the National Library of Medicine of the United States (PubMed) and Elsevier and ScienceDirect databases.As a result of this bibliographic survey, information was obtained that described important aspects related to the investiga-tion with the patient for better orientation and pharmaceutical care. The facial anam-nesis form developed after the study of these articles includes the characterization of the participants, their medical and dermatological history, their skin care routine, life-style, and health habits, as well as the objectives and expectations of the patients regarding their dermatological treatment. It is a tool for pharmaceutical professionals who work in health and aesthetics, which will allow them to understand the patient's needs in its totality, admitting an active role in guiding the patient regarding the cor-rect use of these products. DOI:https://doi.org/10.56238/sevened2023.004-034